Effects of Job Entry Restrictions on Economic Integration - Evidence for Recent Ethnic German Immigrants - Jan Brenner (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2007)
We analyze the impact of job entry restrictions on the economic integration of recent ethnic German immigrants, using twelve waves of the German Socio-Economic Panel.The German labor market closely ties job accessibility to vocational education which likely hampers the transferability of foreign human capital. To assess this effect, we compare the job mismatch probabilities of ethnic German immigrants and German natives and the employment probability in jobs that vary by the qualifications they require. Our results suggest that ethnic Germans are disadvantaged upon arrival, yet almost completely assimilate to comparable natives considering these two job quality measures. Furthermore, controlling for these factors explains a considerable share of the earnings gap between ethnic and native Germans.
Keywords: F22; J61; J62; 330; Human capital transferability and investment; job mismatch; skill requirements; immigrants; wage assimilation; Migranten; Deutsche; Ethnische Gruppe; Berufliche Integration; Markteintritt; Humankapital; Matching; Schätzung; Deutschland